USE OF NEW PEDAGOGICAL TECHNOLOGIES IN TEACHING ECONOMIC AND SOCIAL GEOGRAPHY OF WORLD COUNTRIES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article examines the integration of new pedagogical technologies in the teaching of economic and social geography, their impact on the learning outcomes of students. Using mixed methods, the study evaluates the effectiveness of interactive maps, virtual tours, and collaborative online platforms in creating educational experiences. The results show increased student engagement, critical thinking skills, and overall satisfaction, highlighting the importance of using technological advances in teaching in today's global economic and social landscapes.